WATTPAD’S ROLE IN NARRATIVE WRITING BY INFORMATICS STUDENTS AT ASAHAN UNIVERSITY - Derliana Hasibuan; Rahma Fithriani; Saiful Anwar Matondang; Amirul Mukminin (TELL - US JOURNAL, 2025)
This case study examines the role of Wattpad in enhancing the narrative writing skills of fourth-semester students at the University of Asahan. In the digital age, platforms like Wattpad have become an essential tool in modern education, providing an interactive space for students to engage in creative writing. The study aims to explore how Wattpad motivates students, improves their writing fluency, and offers a platform for feedback and community interaction. Data were gathered through surveys and interviews with students enrolled in narrative writing courses, revealing their experiences using Wattpad as a tool for both academic and personal writing development. The findings indicate that Wattpad serves not only as a motivational resource but also helps students refine their storytelling techniques, expand their vocabulary, and develop their unique writing voices. The study concludes that incorporating Wattpad into the curriculum could significantly enhance narrative writing skills among university students, offering a dynamic and engaging platform for skill development.